Teacher Preparedness and Communicative English Learning Among Young Learners in Central Lombok - Desi Herayana; Baiq Annisa Shallaita; Thalia Qaulan Tsaqiila; Nur Madina Ramadhan (Jurnal Ilmiah Telaah, 2026)
This study examines teacher preparedness in primary English language teaching in Central Lombok. It focuses on teachers’ motivation, teaching experience, professional support, classroom practice, and the challenges that shape young learners’ opportunities for communicative English learning. The study adopted an ethnographically informed qualitative design. Data were collected through classroom observations, interviews, and focus group discussions with six primary school English teachers. The data were analyzed thematically through coding, categorization, and triangulation across data sources. The findings show that teachers had strong motivation to teach English because they recognized its value for students’ future learning opportunities. However, classroom practice remained dominated by drilling, vocabulary memorization, direct translation, and textbook-based exercises. Limited teaching experience, lack of sustained professional development, and restricted classroom facilities constrained teachers’ ability to apply communicative activities. The study argues that improving primary English learning in rural school contexts requires practical teacher training, teacher learning communities, instructional media support, and locally responsive education policy.